Goal Setting Among People Living with Mental Illness: A Qualitative Analysis of Recovery Camp. (4th May 2017) - Moxham, Lorna; Taylor, Ellie K.; Patterson, Christopher; Perlman, Dana; Brighton, Renee; Heffernan, Tim; Sumskis, Susan
ABSTRACT: People living with mental illness (consumers) often experience difficulty in achieving life goals, particularly those important for their recovery. An innovative approach to address consumers' goals for recovery can be found in the form of therapeutic recreation (TR) initiatives. Recovery Camp is a five-day TR program, bringing together people with a serious mental illness, undergraduate health students, and staff members. This article aims to examine the types of goals set by consumers in the context of Recovery Camp, and to what extent the self-identified goals were attained. The consumers ( n   =  27) were invited to set goals that they wished to achieve during the week. On the final day of Recovery Camp, each participant rated the degree to which they felt that each of their goals was achieved or not. The goals were themed using content analysis, revealing four key themes: connectedness, developing healthy habits, challenging oneself, and recovery. All goals were, to some extent, attained. The results suggest people with a mental illness are able to both set and evaluate the self-identified goals in the context of a TR initiative. A collaborative recovery approach indicates that goal planning should be undertaken in direct consultation with the consumer.